Speech Development in Cleft Palate with and without Robin Sequence. Issue 2 (February 2022) - Naros, Andreas; Bartel, Sylva; Bacher, Margit; Koos, Bernd; Blumenstock, Gunnar; Wiechers, Cornelia; Poets, Christian F.; Reinert, Siegmar; Krimmel, Michael
Abstract : Background: Robin sequence is defined as the triad of micrognathia, glossoptosis, and upper airway obstruction. In up to 85 percent, it is associated with cleft palate. Many studies have reported worse speech development in Robin sequence children after cleft palate repair. The authors investigated speech development in isolated Robin sequence with cleft palate versus children with cleft palate only at the age of 5 to 6 years. Methods: All Robin sequence children were treated with the Tübingen palatal plate after birth. Data were collected using the German version of the Great Ormond Street Speech Assessment. Audio and video recordings were reviewed and analyzed separately by two blinded senior phoniatricians based on the German version of the Universal Reporting Parameters for Cleft Palate Speech, and scored to enable comparability of speech outcomes. Results: Forty-four children (Robin sequence, n = 22; cleft palate only, n = 22) were included. Robin sequence children were significantly older at surgery (11.8 months versus 7.1 months; p < 0.001) but younger at study (70.5 months versus 75.2 months; p = 0.035). They also had more severe cleft of the palate ( p = 0.006). All children studied showed good to very good speech development without serious impairment. None of the reported parameters on the German version of the Universal Reporting Parameters for Cleft Palate Speech showed significant group differences; the median total score in the Robin sequence group was 23 (interquartile range, 16.5 to 27.5) versus 19 (interquartile range, 17 to 23) in the cleft palate–only group. Statistical analysis revealed no significant effect of group ( Z = −1.47; p = 0.14). Conclusions: No group differences in speech development were found at age 5 to 6 years. Isolated Robin sequence does not necessarily represent a risk for impaired speech development. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.